2012
DOI: 10.1007/s00125-012-2801-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of hypovitaminosis D-induced islet dysfunction and insulin resistance through direct suppression of the pancreatic islet renin–angiotensin system in mice

Abstract: Aims/hypothesis Vitamin D is necessary for normal insulin action and suppresses renin production. Increased renin-angiotensin system (RAS) activity causes islet damage, including reduced insulin secretion. We therefore sought to determine whether hypovitaminosis D-induced upregulation of islet RAS in vivo impairs islet cell function and increases insulin resistance, and whether pharmacological suppression of the RAS during continuing vitamin D deficiency might correct this. Methods C57BL/6 mice were rendered v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 52 publications
(62 reference statements)
0
35
1
2
Order By: Relevance
“…IU/kg). 13 This contrary result could be explained by a differing capacity of female mice 13 to respond to dietary vitamin D (as compared to the results obtained using male mice described above 11,12 In other studies, we observed no significant effect of lower doses of dietary vitamin [33][34][35] with the VDR -/-mice also exhibiting reduced fasting glucose and insulin levels. 33 The VDR may also be important for mediating the progression of non-alcoholic fatty liver disease (NAFLD) and insulin resistance as reduced hepatic steatosis and triglyceride levels were observed in apoE -/-VDR -/-mice fed a high fat diet.…”
contrasting
confidence: 90%
“…IU/kg). 13 This contrary result could be explained by a differing capacity of female mice 13 to respond to dietary vitamin D (as compared to the results obtained using male mice described above 11,12 In other studies, we observed no significant effect of lower doses of dietary vitamin [33][34][35] with the VDR -/-mice also exhibiting reduced fasting glucose and insulin levels. 33 The VDR may also be important for mediating the progression of non-alcoholic fatty liver disease (NAFLD) and insulin resistance as reduced hepatic steatosis and triglyceride levels were observed in apoE -/-VDR -/-mice fed a high fat diet.…”
contrasting
confidence: 90%
“…[12] and insulin action [13,14], as well as components of inflammation [34,35] and all of these may have an influence on insulin resistance (IR) and development of T2DM. Vitamin D may modulate the local pancreatic islet renin-angiotensin system (RAS) whilst improving islet beta cell secretory function and prevents or can correct induction of RAS component production under conditions of metabolic stress in vitro studies [36,37].…”
Section: Resultsmentioning
confidence: 99%
“…§ §Data missing for 10 subjects. (32). Upon renin-angiotensin system inhibition, the islets' function improved in mice with diabetes, thus leading to a hypothesis that vitamin D supplementation might improve islet cell function before too much damage occurs in the islet cells (32).…”
Section: Discussionmentioning
confidence: 99%